1ISG-014 Real-world analysis on the economic value of reaching lipid target. (23rd March 2022) - Degli Esposti, L; Borghi, C; Galvani, M; Giacomini, E; Manotti, P; Marra, A; Passaro, A; Perrone, V; Pieraccini, F; Sangiorgi, D; Navazio, A
Abstract : Background and importance: To date, little evidence has been reported on the economic burden of patients treated with lipid-lowering drugs without reaching cholesterol control. Aim and objectives: The study aimed to evaluate the healthcare direct costs for the Italian National Health System of patients treated with lipid-lowering drugs that do not achieve the low-density lipoprotein (LDL)-cholesterol target compared to those reaching their targets, and to analyse costs according to the distance from the LDL target using real-world data. Material and methods: An observational analysis was performed on administrative and laboratory data from selected Italian healthcare departments. Patients were included if they presented at least one laboratory LDL test between 2012 and 2019 and if they were prescribed lipid-lowering drugs during the 6 months prior the last LDL detection (index date). Mean annual direct costs were evaluated in the 12 months before the index date in terms of all drugs prescribed, all-cause hospitalisations and all outpatient services. Distance to LDL target was calculated as the difference between the index LDL level and LDL target. Results: Data reproportioned on the Italian population estimated there to be around 4 million patients prescribed lipid-lowering drugs and with a LDL test. Total mean annual healthcare direct cost for patients that did not reach LDL target was higher compared to total cost of patients achieving LDL target (€3678 vs €2906). Costs were mainly driven by hospitalisation (€1330) followed by drugs expenditure (€1012) and outpatient services (€563). Mean total annual healthcare costs increased with the distance from LDL target, specifically from €3004 for patients with 10% distance from LDL target up to €4823 for those 50% or more distance from LDL target. This trend was particularly evident for the cost item related to hospitalisation that went from €1486 to €2819 moving from 10% to ≥50% distance from LDL target. Conclusion and relevance: Results from this real-world study highlighted the higher economic burden for patients that do not reach the therapeutic LDL target that tend to rise along with increasing distance from the LDL target. Overall, our findings could suggest that reducing the distance from the LDL target could have a positive impact also on the economic outcomes for these patients. References and/or acknowledgements: Conflict of interest: No conflict of interest